Bilateral lung transplantation during pregnancy after ECMO for influenza‐A caused ARDS. Issue 10 (9th August 2021) - Foessleitner, Philipp; Hoetzenecker, Konrad; Benazzo, Alberto; Klebermass‐Schrehof, Katrin; Scharrer, Anke; Kiss, Herbert; Farr, Alex
Abstract : Pregnant women with influenza‐A have an increased risk of developing acute respiratory distress syndrome (ARDS). Extracorporeal membrane oxygenation (ECMO) can be used as salvage therapy, with lung transplantation as a therapeutic option. However, successful bilateral lung transplantation during pregnancy has never been reported before. We herein report the case of a 34‐year‐old primipara, who was diagnosed with ARDS caused by influenza‐A‐induced pneumonia at early gestation. After considering all possible therapeutic options and being fully dependent on VV‐ECMO support, she underwent bilateral lung transplantation. The transplantation with intraoperative central VA‐ECMO support was successfully performed with good recovery after an initial primary graft dysfunction. The pregnancy was prolonged until 29 +5 gestational weeks. The newborn exhibited growth retardation and was initially stabilized, but later died due to severe, hypoxic respiratory failure and pulmonary hypertension. In conclusion, lung transplantation is a possible salvage therapy for patients with severe lung failure following ARDS during pregnancy. However, it places the mother and unborn child at risk. A multi‐professional approach is warranted to diagnose and treat complications at an early stage. Abstract : This case report of successful bilateral lung transplantation during pregnancy shows that lung transplantation is a possible salvage therapy for pregnant women with severe lung failure.